PERBEDAAN SIKLUS MENSTRUASI BERDASARKAN INDEKS MASSA TUBUH PADA SISWI SMA NU 1 MODEL KABUPATEN LAMONGAN - Nisa’, Khoirun; Widiatrilupi, Raden Maria Veronika; Alfitri, Rosyidah (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
According to WHO data, 75% of women experience menstrual disorders, approximately 60-70% of women with underweight and overweight can show symptoms of menstrual cycle disorders. Based on data from Basic Health Research (Riskesdas) in 2018, the percentage of women in East Java who experience irregular menstrual cycles is 13.3% with the total number of women who experience irregular menstrual cycles in Indonesia at 13.7%. Female students with an abnormal body mass index can cause disruption to the menstrual cycle. The aim of this research was to determine differences in menstrual cycles based on Body Mass Index in female students at SMA NU 1 Model Lamongan. This research design uses a cross sectional study design. The population and sample in this research were 50 respondents from SMA NU 1 Model Lamongan using total sampling technique. Data were collected by measuring height and weight and questionnaires. Most respondents had a normal menstrual cycle (62%) had a normal body mass index (58%). Meanwhile, the research results showed that the majority of thin (12%) and fat (30%) respondents with an abnormal BMI category experienced irregular menstrual cycles (lengthening & shortening). Analysis univariate and bivariate data analysis using Spearman's Rank. Based on the results of statistical tests, it is known that there are differences in menstrual cycles based on body mass index with a value of p = 0.00. Female students with an abnormal menstrual cycle have an abnormal body mass index (thin & fat) while female students with a normal menstrual cycle tend to have a normal body mass index as well. It is hoped that female students who have an abnormal body mass index must pay attention to their eating patterns. healthy and good nutritional intake.